Improving WASH facilities and practices in Bangladeshi schools: progress and challenges from 2014 to 2018 - Farjana Jahan; Noshin Sayiara Shuchi; Afsana Yeamin; Titly Sen; Abul Kasham Shoab; Mahbub-Ul Alam; Supta Sarker; Mehjabin Tishan Mahfuz; Mahadi Hasan; Hasin Jahan; Khairul Islam; Md. Masud Alam; et al. (Global Health Action, 2025)
Background In low- and middle-income countries like Bangladesh, inadequate water, sanitation, and hygiene (WASH) practices lead to a higher disease burden among children and hinder their academic performance. However, there have been efforts to improve WASH between 2014 and 2018. Objectives The study aimed to investigate changes in WASH facilities and practices in Bangladeshi schools from 2014 to 2018. Methods We analyzed pooled data from Bangladesh National Hygiene Survey 2014 and 2018. We performed descriptive analysis, bivariate analysis, and multivariate Generalized Estimating Equation (GEE) to analyze the changes over the four years time period. Results Results showed that basic drinking water services increased from 78% in 2014 to 90% in 2018. Schools showed a significant increase in basic sanitation services from 19% in 2014 to 52% in 2018. We discovered that students’ access to water and soap increased from 2014 to 2018, from 21% to 35%. In the GEE model, we found that change in time, non govt urban schools were associated factors with improved basic drinking water services. For basic sanitation services, changes in time, school type and area type were significantly associated higher services. And for basic hygiene services, the associated factors were: schools having hygiene promotion visits, and availability of hygiene brigades at schools managed by students. Conclusion WASH services in Bangladeshi schools have improved significantly, yet disparities exist, particularly in government and rural schools. Although students’ knowledge improved, their practices still need improvements through training on proper WASH practices.